POLAROGRAPHIC METHOD VERSUS ANALYTICAL METHOD IN DETERMINATION OF DISSOLVED OXYGEN AND N-NO3 - N. Razeghi; Gh. Jamshidinia; M. Hakimipour (Tehran University of Medical Sciences, 1976)
Polarographic method is considered as an alternative laboratory technique for analytical method in determination of dissolved Oxygen and N-N03. Analytical method is a time consuming technique and is subject to several interferences due to some of constituents in sewage. In this laboratory research, the polar graphic technique with, mercury drop electrodes and titrometric method were applied in determination of dissolved Oxygen and N.N93 of several samples. Statistical analysis of the results indicates that coefficient of correlation of the results of the titrometric method to the standard in 0.9992822 while in the case of polarographic method is 0.9994417. Therefore, polarographic determination of dissolved Oxygen and N.N03 can be considered as an accurate and dependable technique. The works on 22 samples of domestic sewage in this research revealed that polarographic technique can be used just as well for determination of biochemical Oxygen demand.